2010
DOI: 10.2174/157488810793351668
|View full text |Cite
|
Sign up to set email alerts
|

Human Umbilical Cord Blood as an Emerging Stem Cell Therapy for Diabetes Mellitus

Abstract: Cellular therapy for patients with diabetes is receiving great attention among scientists and clinicians. Bone marrow is considered one of the rich sources of stem cells. However, the limited availability of bone marrow donors precludes its use for all the suitable patients. Human umbilical cord blood (HUCB) is being increasingly used as an alternative source of stem cells for cell-based therapy for malignant and nonmalignant diseases. HUCB is preferred to bone marrow because of its easy availability, low pote… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
8
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(8 citation statements)
references
References 38 publications
0
8
0
Order By: Relevance
“…Our previous study also found that UCBC treatment could significantly improve gross motor function measure (GMFM) scores in patients with severe cerebral palsy, especially in supine, prone, and sitting functions [ 15 ]. The transplantation with UCBCs without full HLA matching still had lower incidences of GVHD, graft-versus-leukemia (GvL), and tumorigenicity as well as infectious complications in other circumstance reported by previous studies [ 23 , 24 ]. In our clinical trial circumstance, allogeneic UCBSCs without full HLA matching in absence of immune suppression/myeloablation to treat nonhematopoietic conditions showed to be even safer than those mentioned before [ 25 ].…”
Section: Discussionmentioning
confidence: 88%
“…Our previous study also found that UCBC treatment could significantly improve gross motor function measure (GMFM) scores in patients with severe cerebral palsy, especially in supine, prone, and sitting functions [ 15 ]. The transplantation with UCBCs without full HLA matching still had lower incidences of GVHD, graft-versus-leukemia (GvL), and tumorigenicity as well as infectious complications in other circumstance reported by previous studies [ 23 , 24 ]. In our clinical trial circumstance, allogeneic UCBSCs without full HLA matching in absence of immune suppression/myeloablation to treat nonhematopoietic conditions showed to be even safer than those mentioned before [ 25 ].…”
Section: Discussionmentioning
confidence: 88%
“…It is evidenced that MSCs from foetal sources, when compared to adult sources, creates a large population of immature unprimed highly functional regulatory T lymphocytes [19]. These regulatory T cells are reported to help decrease the inflammatory cytokine response that instigates diabetes.…”
Section: Discussionmentioning
confidence: 99%
“…MSCs are multipotent, self-renewing cells that not only are primarily localized in the bone marrow but can also be isolated from other tissues, including adipose tissue [17], skeletal muscle [18], amniotic fluid [19], and umbilical cord blood [20]. Moreover, MSCs can be expanded for several passages without losing their self-renewing capacity [21].…”
Section: Mesenchymal Stem Cellsmentioning
confidence: 99%
“…Although these were only preliminary results, Timper et al reported that insulin-producing cells could be generated from adipose-derived MSCs [44]. Finally, the human umbilical cord blood is another source of stem cells with the potential to develop into insulin-producing cells, even in vivo [20].…”
Section: Mesenchymal Stem Cell Sources and Safetymentioning
confidence: 99%